Testing the weak-form efficiency of agriculture’s capital markets - Ghimire, Binam; Annussek, Kolja; Harvey, Jackie; Sharma, Satish (Economics and Business Review, 2016)
This paper investigates the empirical validity of the weak-form Efficient Market Hypothesis [EMH] in global equity markets for agriculture. We examine whether developed agriculture markets are more efficient than emerging agriculture markets. We test six agriculture and food chain indices over the period of time between 2010 and 2013. The weak EMH was tested using the parametric Augmented Dickey-Fuller test as well as the non-parametric Runs test and Autocorrelation function test. The parametric test suggested some evidence for the existence of the weak-form EMH for all six indices in at least some of the five tested periods. However the non-parametric tests clearly proved the inefficiency of all indexes during all periods. Thus we finally rejected the null hypothesis for all indices in all periods. Accordingly agriculture’s developed markets are equally inefficient and predictable as its emerging markets. The results of this work suggest that investors can achieve superior returns by investing in agricultural equity markets following a technical analysis and active portfolio approach. Thus this work is in great interest of investors and portfolio managers following an agriculture strategy. The study adds value to current research of market efficiency in developed as well as emerging markets.